Headaches associated with acute SARS-CoV-2 infection: A prospective cross-sectional study. (October 2021) - Souza, Delon D; Shivde, Sonia; Awatare, Poonam; Avati, Amrutha; John, Saji K; Badachi, Sagar; Nadig, Raghunandan; Sarma, GRK; Mathew, Thomas
Objectives: The prevalence and characteristics of COVID-19-related headaches are not known in Indian patients. We aim to determine the prevalence and characteristics of headache in COVID-19-infected individuals and make a comparison with those without headaches. Methods: This prospective cross-sectional observational study was conducted from 1 October to 31 October 2020. Data were collected using a detailed questionnaire. We compared the data of those with and without headaches to identify the differences between the groups. Results: During the study period of 1 month, among 225 COVID-19-infected patients, 33.8% patients had headaches. The mean age of patients with headache was 48.89 ± 15.19 years. In all, 53.9% were females. In 65.8%, headache occurred at the onset of viral illness; 44.7% described the headache as dull aching; 39.5% had bifrontal headache; and 32.9% had holocranial headache. In total, 78.9% had complete resolution of headache within 5 days. A comparison between those with and without headaches showed that those with headaches were more younger (48.89 ± 15.19 vs 54.61 ± 14.57 years, p = 0.007) and of female gender (41/76(53.9%) vs 41/149 (27.5%), p = 0.001). Primary headache disorders were more common in the headache group. Levels of inflammatory markers such as leukocyte count (7234.17 ± 3054.96 vs 8773.35 ± 5103.65, p = 0.017), erythrocyte sedimentation rate (39.28 ± 23.29 vs 50.41 ± 27.61, p = 0.02) and ferritin (381.06 ± 485.2 vs 657.10 ± 863.80, p = 0.014) were lower in those with headaches. Conclusions: Headaches are a common and early symptom of acute SARS-CoV-2 infection more frequently seen in young females and in those with a history of primary headache disorders. The lower level of inflammatory markers in those with headaches suggests that these headaches are probably due to the local spread of virus through the trigeminal nerve endings, resulting in activation of the trigeminovascular system.